Proporsi Pessimum dan Ekspansi - Mohd. Isneini (UNIVERSITAS LAMPUNG, 2016)
Expansion in mortar or concrete could happen due to chemical reaction inside it. Some various proportion of reactives aggregate with non reactive aggregates were combined to get maximum expansion in mortar. Mortar without combining aggregates was also made to find out its reactivity. Mortar was cast based on JIS A 1146. Mortar specimens were cured in controlled room with temperature 40 O C dan Relative Humidity 100 O C. The Results showed that when reactive aggregates were used in proportion 30:70 with non reactive aggregates then the expansion was maximum.